Yemen's humanitarian collaboration during conflict: UN and local NGOs in focus - Moosa Elayah (18134107) (2024)
This paper presents an exploratory study investigating the complex relationship between the United Nations (UN) system and local non-governmental organizations (NGOs) in Yemen's humanitarian food assistance provision. Employing qualitative research methods, including document analysis and stakeholder interviews, we aim to understand key factors influencing collaboration and identify challenges hindering effective cooperation. Our findings emphasize the need for the UN to diversify its approaches to social interaction in food aid programs, prioritizing initiatives that resonate with local communities. Furthermore, active efforts to engage and satisfy local NGOs are essential for improving program effectiveness and achieving shared objectives. This study sheds light on critical areas for intervention, emphasizing the importance of fostering meaningful partnerships to address humanitarian challenges in Yemen. Other Information Published in: World Development Perspectives License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.wdp.2024.100585